ASSESSMENT OF CAUSES OF MATERNAL DEATH IN 1 YEAR AT A TERTIARY CENTER OF CENTRAL INDIA - NAAGAR, JAGRATI KIRAN; SHRIVASTAVA, PRANJAL; SHRIVASTAVA, RAGINI; SINGH, PUNYA PRATAP; MISHRA, SHRADDHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: According to the definition of maternal mortality, it is the “death of a woman while pregnant or within 42 days following termination of pregnancy, irrespective of the site and duration of pregnancy, from any cause connected to or aggravated by the pregnancy or its management but not by accidental or incidental cause.” Studying maternal mortality and factors contributing to maternal deaths at Bundelkhand Medical College for 1 year from January 2021 to December 2021 to identify causes that can be avoided and use the knowledge, thereby produced to lower maternal mortality. Methods: A retrospective cross-sectional study of all maternal deaths from January to December 2021. The causes of death and the time between admission and death for each maternal death were thoroughly examined. Results: The Maternal mortality ratio in the present study was found to be 357.7/100,000 live births for the year 2021. Antepartum eclampsia was found most prevalent cause of maternal mortality in 39% cases. Other causes were pregnancy induced hypertension, severe anemia, retained placenta, hepatitis with multi organ failure, septic shock, and ruptured uterus. Conclusion: Maternal mortality is indicator of health-care services of a nation. Better awareness and early referral can help in reducing maternal mortality significantly.